Formal Total Synthesis of (−)-Isolaurallene and Structure Determination of (+)-4-epi-Isolaurallene via Stereodivergent Intramolecular Amide Enolate Alkylation - Park, Youngjik; Jang, Hongjun; Kwak, Soo Yeon; Lim, Seongju; Lee, Dongjoo; Kim, Hyoungsu; Kim, Deukjoon (Organic Letters, 2025)
Described herein are the formal total syntheses of (−)-isolaurallene (1) and structure determination of newly isolated (+)-4-epi-isolaurallene (2) via a highly stereodivergent intramolecular amide enolate alkylation (IAEA) strategy. Highly stereoselective constructions of α,α′-trans-THF 3 and α,α′-cis-THF 4 were accomplished by subjecting common intermediate 5 to non-chelate-controlled and chelate-controlled IAEA, respectively. The former protocol greatly improves the moderate stereoselectivity previously observed in constructing α,α′-trans-THF rings via intramolecular nitrile anion alkylation (INAA).